Butterfly diversity and abundance with reference to habitat heterogeneity in Calbayog Pan-As-Hayiban Protected Landscape, Samar, Philippines - Bayani, Koreen C. (2022)
In ecosystems, butterflies belonging to the macrolepidoptera group of Lepidoptera are best used as indicator taxon to assess environments under stress from habitat fragmentation, degradation, and climate change. The diversity and abundance of butterflies with reference to habitat heterogeneity in Calbayog Pan-As-Hayiban Protected Landscape, Samar, was assessed in two different habitat types: open forest and riparian. The butterfly census technique included a Pollard walk method with the necessary modification. A total of 37 butterfly species belonging to 5 families were identified, representing only 3.9% of the 927 butterfly species in the Philippines. Seventeen of the total species identified were endemic to the country. Nymphalidae (19 species, 51%) was the most dominant family. High diversity of butterfly species was recorded in riparian habitat (H'=3.25), while moderate diversity was observed in the open forest (H'= 2.79). Species composition of butterflies with reference to the heterogeneity showed a significant difference (p<0.05). Higher species diversity and richness in riparian was observed due to a more varied secondary vegetation, where availability of diverse plants and access to host plants were observed. The butterfly community was also significantly associated with light intensity, temperature, and humidity. Long-term monitoring of butterflies is recommended to give a better representative sample in different habitat types which are not extensively sampled.